PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI Di KANTOR UPTD PENDIDIKAN KECAMATAN PELEPAT HILIR KABUPATEN BUNGO - -, ILYAS MADI (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2015)
Office UPTD Pelepat Ilir Bungo district had planned to send 14 employees to participate in education and training. With the implementation of education and training to employees UPTD Office Pelepat Ilir Bungo district is expected to improve the performance of employees is seen from the quantity of work, quantity of work and job performance in the job.Based on the background and the extent of the problem mentioned above, the formulation of the problem in this study is: